Using Tools Lean Accounting to Reduce the Costing: An Applied Research in General Company for Electric Industry (Journal of Accounting and Financial Studies ( JAFS ), 2013)
The developments accelerated in technology and rapid changes in the environment and increase numbers industrial countries and different desires and requirements of customers, lead to be produced in large quantities is not feasible due to changes listed above as well as the need to product variety and change in tastes and desires of consumers, all above led not to enable companies to discharge their products in the case of mass production and created the need to devise ways and new methods fit with the current situation, and accounting point no longer the traditional accounting systems able to meet the requirements needed by the companies to make decisions and know where waste and loss of resources resulting to invent new style away from the conventional methods currently used is accounting graceful style (Lean Accounting) to keep a place mentioned  with modern developments.On this basis, centered research problem about the possibility of using lean accounting tools General Company for Electric Industries that fit with its production and under its internal and external environment.The objective of this research is to the possibility of applying the tools of Lean accounting in a sample of companies. By using set of  tools.The main results are to calculate production costs and achieve significant cost savings and time cycle of production (working time) and reduce waiting times and conversion and seeking to reduce inventory of raw materials and work in process & finished goods, and other tangible  and  intangible benefits achieved by using Lean accounting methods.The research conclude that applying lean accounting tools have high  capacity to determine the actual cost of production and the elimination of loss in production processes and administrative feasibility of providing accurate and quick information to all users . So the researcher recommends using these tools and recommendations that have been proposed.